Knowledge About Risks, Benefits, and Curative Potential of Immunotherapy Among Patients with Advanced Cancer. (28th August 2021) - Petrillo, Laura A.; Zhou, Ashley Z.; Sullivan, Ryan; Volandes, Angelo; Greer, Joseph A.; Temel, Jennifer S.; El‐Jawahri, Areej
Abstract: Background: Immunotherapy is the first‐line treatment for melanoma and lung cancer and brings new risks of immune‐related adverse events. We aimed to describe patients' knowledge about risks, benefits, and goals of immunotherapy. Materials and Methods: We conducted a cross‐sectional study of patients with advanced melanoma or non‐small cell lung cancer that used a 9‐item knowledge survey and questions from the Prognosis and Treatment Perceptions Questionnaire. Results: We surveyed 105 participants (57 with melanoma, 48 with lung cancer) with median age 69 years (range 36–89). Participants' responses revealed knowledge deficits about immunotherapy mechanism of action and lack of awareness about the timing and severity of side effects. One third (34%; 36/105) of participants reported that the primary goal of their treatment is to cure their cancer. Conclusion: Given the widespread use of immunotherapy, patients would benefit from educational tools so that they know what to expect regarding side effects and prognosis. Abstract : Individual experiences with immunotherapy are varied. This article describes patients' knowledge about the risks, benefits, and goals of immunotherapy treatment.